Nototanaids (Crustacea: Tanaidacea) from Japan, with the description of a new species of Nototanoides - Kakui, K., & Yamasaki, H. (Species Diversity, 2013)
We describe a new nototanaid, Nototanoides ohtsukai sp. nov., based on specimens from the Yaku-Shin-Sone Bank,Nansei Archipelago, southern Japan (North Pacific Ocean). This species differs from its only congener, N. trifurcatus Sieg and Heard, 1985, in having a short distal article in the antennule and in the position of a row of aesthetascs on that article. We also present a partial redescription of the nototanaid Paranesotanais longicephalus Larsen and Shimomura, 2008 and a key to the genera of the families Nototanaidae and Tanaissuidae.